Improving the Impact of Bio-Based Plastic Materials on Baby Products from a Circular Economy Perspective Toward Business Operations: A Case Study at PT. XYZ - Samodro, Aryudhono; Purwanto, Purwanto (Journal of International Conference Proceedings, 2025)
Bio-based plastic material is one of the non-fossil materials that gain popularity these days. This kind of material is made from renewable energy that helps to reduce the waste that impacts on the environment. Despite its popularity, this material procurement is also another challenge due to its rare manufacturers or suppliers and impacts the overall procurement cost and time consuming. This case study aims to evaluate and assess the impact of using bio-based plastic material in the manufacturing processes of baby products and its subsequent effect such as: productivity, quality, cost, product sustainability and the market acceptance at PT. XYZ. The research employs a mixed-methods approach, combining qualitative analysis of manufacturing productivity metrics with market trend analysis. Preliminary findings at PT. XYZ found that the use of biobased plastic material can reduce the manufacturing productivity due to its difficulty of processing and cost-effectiveness. This research concludes with a discussion on the implications of these findings and the solutions for manufacturers, marketers, and policymakers in the baby products industry, and suggests directions for future research improvement.